Organic Farming on the Urban Fringe and the Factors Affecting Its Continuity: The Case of Bursa - Seckin, Ebru; Kozaman Aygun, Senem (UNIV NAMIK KEMAL, 2025)
In recent years, the rapid expansion of urban areas and the concomitant reduction in agricultural land have raised concerns about food security. Access to healthy food has emerged as a significant concern, particularly in metropolitan areas where locally produced food is limited. The sustainability of agricultural land in the urban fringe and the search for solutions to improve local food systems are prominent issues on the agendas of many countries. In this context, the objective of the article is to gain insight into the development of organic farming activities in the periphery of metropolitan cities, in the case of Bursa. The study's objective was to ascertain the spatial characteristics of organic production in Bursa. Furthermore, a survey was conducted with organic producers to ascertain the micro-scaled factors influencing the continuity of organic agriculture, employing the decision tree model. Consequently, the organic production in Bursa is dispersed, characterized by small-scale enterprises, and concentrated in rural settlements around Uluda & gbreve;. The analysis indicates that the primary factor influencing the continuation of organic production in the province is the age of the producers. An examination of the structure of organic production reveals that peasant farmers conduct organic production with a traditional agricultural background at the request of the buyer company. While this relationship model appears beneficial for small producers in maintaining organic agriculture, it does not result in a change in income or skills for small producers. Instead, it creates a dependency on the buyer, and farmers cannot fulfill the requirements of organic agriculture without external support. As a result, these producers may revert to conventional production from organic production. In Bursa, a limited number of large-scale organic producers control the entire production process. These producers demonstrate greater resilience in the sector and a stronger inclination to continue organic farming than their contracted counterparts. Consequently, it is evident that human and social capital must be reinforced and that agricultural subsidies are invaluable in mitigating the vulnerability resulting from the scarcity of social and financial resources in the region where small-scale enterprises are concentrated. Furthermore, it is essential to transform organic agriculture into a social practice involving young producers.
Keywords: Organic farming; Local food systems; Bursa; Turkiye; FARMERS; SECTOR; AGRICULTURE; ADOPTION